Congenital Giant Melanocytic Nevus with Malignant Melanoma of the Pleura: Do Primary Pleural Melanomas Exist? - Brijesh Sharma; Desh Deepak; Mohammed Ali; Mahender Singh Rajput; Rajni Parmar; Rajesh Taneja (Middle East Journal of Cancer, 2017)
Cases of primary pleural and bronchial melanoma have been described in the literature in the absence of melanocytic cells in the pleura and bronchi. We described a case of congenital giant melanocytic nevus that had a presentation suggestive of primary pleural melanoma. However, biopsy of a chest wall lesion confirmed the presence of another melanoma deposit in a subcutaneous swelling concealed within the congenital giant melanocytic nevus. Histopathology with immunohistochemistry results showed that the pleural and chest wall swelling were similar. The difficult clinical detection of the primary tumor contributes to the fact that 24% of cases of congenital giant melanocytic nevus receive a diagnosis of metastatic melanoma without identification of the primary site. We propose that it is probable that the entity “primary pleural melanoma” may, in fact, not exist. Instead, all such reported tumors in the pleura may actually be metastatic from an unknown, regressed, or missed primary site.